2009
DOI: 10.1590/s1516-89132009000500008
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and anti-inflammatory properties of essential oil from Ageratum fastigiatum

Abstract: The chemical composition, analgesic and anti-inflammatory properties of essential oil from Ageratum fastigiatumwere investigated. The main compounds found in the essential oil were germacrene D, α-humulene and β-cedrene. The oil, with LD 50 of 2.50 g/kg, inhibited the acetic acid-induced writhing at the dose of 200 mg/kg. In the formalin test, the oil inhibited the first phase (200 mg/kg) and the second phase (100 mg/kg and 200 mg/kg). In the hot plate test, after 30 and 60 min of treatment the doses of 100 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…In the current study the β-cedrene was not detected, the α-humulene appear in small amount (1.35%) and the germacrene D was not majority terpene (9.09%), being the α-pinene (51.27%) the main component observed. More abundant components in our research (trans-β-caryophyllene, β-pinene and β-ocimene) were not detected by Del-Vechio-Vieira et al (2009a). Among the factors that could influence those differences between the two researches we can mention the use of fresh material in our study and the use of dry leaves on the previous work.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…In the current study the β-cedrene was not detected, the α-humulene appear in small amount (1.35%) and the germacrene D was not majority terpene (9.09%), being the α-pinene (51.27%) the main component observed. More abundant components in our research (trans-β-caryophyllene, β-pinene and β-ocimene) were not detected by Del-Vechio-Vieira et al (2009a). Among the factors that could influence those differences between the two researches we can mention the use of fresh material in our study and the use of dry leaves on the previous work.…”
Section: Resultsmentioning
confidence: 55%
“…The analysis of essential oils of this species revealed the sesquiterpenes prevalence; however, qualitative and quantitative differences are observed in their composition when derived from different tissues or individuals (Del-Vechio-Vieira et al, 2009a;DelVechio-Vieira et al, 2009b). Those variations in secondary metabolites are influenced by intrinsic factors (genetics, development, growth, vegetable organ) and extrinsic (atmospheric conditions, geographic region, soil type, presence of predators or pathogens, among other environmental factors) to plants Castro et al, 2004;Gobbo-Neto & Lopes, 2007).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…These receptors are recognized as important targets for modulation by sedative, anxiolytic and general anesthetic agents (Franks & Lieb, 1994). Del-Vechio-Vieira et al (2009) described the analgesic activity of EO from leaves of Ageratum fastigiatum in mice, whose main component was germacrene D. Studies regarding this activity related to bicyclogermacrene were not found in literature. To the best of our knowledge this is the first study that describes the anesthetic activity of this EO.…”
Section: Transportation Experimentmentioning
confidence: 99%
“…[27][28][29] Consequently, there is a strong interest in searching for new anti-inflammatory agents from natural products. [30][31][32] Studies on the anti-inflammatory activity of solvent extracts of seaweeds and seagrass have been conducted previously. 16,20,33,34 However, very few studies have investigated the anti-inflammatory activity of sulfated polysaccharides obtained from seaweeds.…”
Section: Discussionmentioning
confidence: 99%